Peran Ekokardiografi sebagai Modalitas Diagnostik Pendukung pada Diseksi Aorta Stanford A Terlokalisir - Haris Munirwan; Amiliana Mardiani Soesanto; Rina Ariani; Taofan Taofan; Suko Adiarto; Ismoyo Sunu; Bagus Herlambang; Dicky Aligheri; Retno Dwi Astuti (The Indonesian Heart Association, 2014)
Ascending Stanford type A aortic dissection carries a high morbidity and mortality. Proper identification of the proximal origin of the dissection and determination of concomitant aortic valve involvement significantly facilitate surgical repair which may improve survival.2Rapid imaging is necessary for the timely diagnosis of a potentially life-threatening condition. Transthoracic Echocardiography is highly accurate for the detection of acute aortic syndromes especially identify ascending aortic pathology such as type A aortic dissection.3 We report the unusual case of 52-years old male who present atypical presentation of aortic dissection with unclear view of dissection by CT Angiography aorta, and diagnosed as Localized Stanford A Aortic dissection with supported data by echocardiography modality.